ANALISIS PEYERAPAN TENAGA KERJA SEKTORAL DI KABUPATEN SORONG (Analisis of Sectoral Employment Absorbtion in Sorong Regency) - Priskila Hosio; Theodora M. Katiandagho; Oktavianus Porajouw (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
The objective of this research is to analyze the absorption of sectoral workers in Sorong Regency. This research was carried out for 3 months, from August to October 2018. The typeÂ of data used in this study is secondary data obtained from the Central Statistics Office of Sorong Regency. The variables measured were GRDP and the number of workers per sector in Sorong Regency from 2010 and 2017. The data analysis used was descriptive analysis. The research results showed that, sectoral employment in Sorong Regency absorbed the most labor, namely agriculture, fisheries and maritime sectors in the first position, the social services sector in the second position and in the wholesale trade sector, restaurants and hotels in the third position.Keywords: Analysis- Sectoral Employment -Absorption